BEARING DOWN ON TREPONEMES: AN ATYPICAL PRESENTATION OF SYPHILITIC UVEITIS. Issue Volume 15:Issues 4(2021) (July 2021) - Cherfan, Daniel G.; Browne, Andrew W.; Deasy, Ryan; Lapinski, James; Srivastava, Sunil K.
Abstract : Purpose: To present an atypical case of syphilis that presented with findings concerning for endocarditis and valsalva retinopathy. Methods: History and clinical examination of 42-year-old white man who presented to the emergency department with acute onset vision changes associated with gastrointestinal symptoms, otalgia, and constitutional symptoms. Results: The review of this case highlights the atypical nature in which syphilis can present and can remain undiagnosed even in the face of extensive workups for other systemic conditions. Conclusion: We present a case of syphilis in a patient with multiorgan involvement in whom the diagnosis was made based on atypical ocular examination findings. Abstract : Syphilitic vasculitis and presumed syphilitic otitis media presenting as valsalva retinopathy